Una revisión de la calidad de agua del cultivo de camarón blanco (litopenaeus vannamei) a baja salinidad. - Celi Quezada, Deivy Ulises (Machala : Universidad Técnica de Machala, 2022)
Low-salinity culture of marine shrimp is a trend with continuous growth in Ecuador and other regions of the world. The Pacific white shrimp (Litopenaeus vannamei) is the main species selected for shrimp farming at low salinity due to its tolerance to wide ranges of this parameter. The quality of water used for shrimp production is considered a relevant factor for the sustainability of the production system. According to the bibliographical analysis carried out in the present work, the optimal physicochemical variables are the following: temperature: 28-31 °C; turbidity no greater than 30 NTU; pH of 7-8.58, alkalinity greater than 100 mg L-1. It has been indicated that the toxicity of nitrogenous compounds increases with decreasing salinity, acceptable values for ammonium 0.26-0.31 mg L-1, nitrite 0.28-0.32 mg L-1, nitrate 0.73-0.77 mg L-1 for lower salinity at 2 ppt. In special reference, potassium is essential for the survival of shrimp at low salinity, specifying that with a salinity of 2 ppt, 50 mg L-1 of potassium is recommended. Additionally, at a salinity of 5 ppt values of 1400 ppm hardness are acceptable. The culture of white shrimp (Litopenaeus vannamei) at low salinity is feasible as long as the water quality parameters are kept within an acceptable range. The current information is focused on the control of the physicochemical parameters of the crop, such as alkalinity, nitrogenous compounds, hardness, pH, temperature, turbidity, etc. Documentation on water management prior to and during cultivation and the presence of phytoplanktonic microorganisms in low-salinity systems is scarce.
El cultivo a baja salinidad de camarón marino es una tendencia con continuo crecimiento en Ecuador y otras regiones del mundo. El camarón blanco del pacífico (Litopenaeus vannamei) es la principal especie seleccionada para el cultivo de camarón a baja salinidad por su tolerancia a rangos amplios de este parámetro. La calidad de agua utilizada para la producción de camarón, se considera un factor relevante para la sostenibilidad del sistema productivo. De acuerdo al análisis bibliográfico realizado en el presente trabajo, las variables fisicoquímicas óptimas son las siguientes: temperatura: 28-31 °C; turbidez no mayor a 30 NTU; pH de 7-8.58, alcalinidad superior a 100 mg L-1. Se ha indicado que la toxicidad de compuestos nitrogenados aumenta con la disminución de la salinidad, valores aceptables para amonio 0.26-0.31 mg L-1, nitrito 0.28-0.32 mg L-1, nitrato 0.73-0.77 mg L-1 para una salinidad menor a 2 ppt. En especial referencia, el potasio es esencial para la supervivencia del camarón a baja salinidad, especificándose que con una salinidad de 2 ppt se recomienda 50 mg L-1 de potasio. Adicionalmente, a una salinidad de 5 ppt valores de 1400 ppm de dureza son aceptables. El cultivo de camarón blanco (Litopenaeus vannamei) a baja salinidad es factible siempre y cuando se mantengan los parámetros de calidad de agua en un rango aceptable. La información actual está enfocada en el control de los parámetros fisicoquímicos del cultivo, tales como alcalinidad, compuestos nitrogenados, dureza, pH, temperatura, turbidez, etc. La documentación sobre el manejo del agua previo y durante el cultivo y la presencia de microorganismos fitoplanctónicos en sistemas a baja salinidad es escasa.
Keywords: CALIDAD DE AGUA; CAMARON BLANCO; BAJA SALINIDAD; PARAMETROS